PENGARUH KONSENTRASI GIBERELIN TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS PADI SAWAH PADA CEKAMAN SALINITAS TINGGI - Roni Assafaat Hadi (Jurnal Agroekoteknologi, 2019)
ABSTRACTThis study aimed to: (1) study the effect of interactions between gibberellin concentration and several wetland rice varieties on conditions of high salinity stress on growth and yield, (2) gibberellin concentration and lowland rice varieties which have the best influence on growth and the results of lowland rice. The research was carried out at the screen house of the Faculty of Agriculture, Winaya Mukti Tanjungsari University - Sumedang Regency with altitude 850 m above sea level. The time of the study was carried out in December 2014 until April 2015. The study used a factorial Randomized Block Design method, which consisted of two factors: gibberellin concentration and several varieties of lowland rice in high salinity stress. The first factor is the concentration of gibberellin (G), consisting of four levels: g0 = soaking the seeds for 24 hours in giberelin 0 mgL-1 = soaking the seeds for 24 hours in gibberellins 20 mgL-1, g2 = soaking the seeds during 24 hours in gibberellins 40 mgL-1, g3 = soaking the seeds for 24 hours in giberelin 60 mgL-1. The second factor is rice paddy variety (P), consisting of eight levels: p1 = Inpari 10, p2 = Inpari 20, p3 = Inpari 25, p4 = Inpari 26, p5 = Inpari 27, p6 = Inpari 30, p7 = Inpara 4, and p8 = Banyuasin. The results of the study indicate that here is an interaction effect between gibberellin concentrations and some lowland rice varieties in high salinity tresses against root drop ratio at ages 7, 35 and 49 HST. Rice varieties independently affect the age of harvest and the weight of 1000 seeds. There is a concentration of gibberellins and lowland rice varieties that produce the best growth and yield in high salinity stress.